Validity and reliability of the Chinese version of the Health Literacy Scale Short-Form in the Chinese population - Sun, Xiaonan; Lv, Ke; Wang, Fei; Ge, Pu; Niu, Yuyao; Yu, Wenli; Sun, Xinying; Ming, Wai-Kit; He, Miao; Wu, Yibo (BMC public health, 2023)
Health literacy is closely related to health status. Measuring public health literacy levels helps to warn of health status and manage health problems through timely interventions. The items of relevant evaluation tools are complex and numerous in China, and there is no recognized health literacy brief scale for the whole population. To translate the 12-item short-form health literacy scale (HLS-SF12) and test the validity and reliability of the Chinese version of the HLS-SF12 in the Chinese population. The HLS-SF12 was translated into Chinese using the procedures of translation, back translation, and cultural debugging. 10,951 residents were selected by quota sampling method to test the validity and reliability of the scale, and 33 people were selected to retest after 2 weeks. The reliability was tested by using internal consistency coefficient and test-retest reliability. The validity was tested by using confirmatory factor analysis, content validity, convergent validity and discriminant validity. The Cronbach's Alpha coefficient for the total scale was 0.94, and the test-retest reliability was 0.89. The Cronbach's Alpha coefficients for the three subscales of health care, disease prevention, and health promotion respectively were 0.86, 0.86, 0.87, and the test-retest reliability respectively were 0.91, 0.79, 0.63. The confirmatory factor analysis identified a three factors model and showed nice goodness of fit indices for Chinese HLS-SF12 (GFI = 0.96, CFI = 0.97, IFI = 0.97, TLI = 0.96, and RMSEA = 0.07). The Chinese version of the HLS-SF12 has good reliability and validity, and can be used as a tool to evaluate the health literacy of Chinese people.